Computer Tools for Diagnosing Citrus Leaf Symptoms (Part 1): Diagnosis and Recommendation Integrated System (DRIS) - Arnold Schumann (EDIS, 2020)
This new 2-page article provides instructions for using the Diagnosis and Recommendation Integrated System, or DRIS, a web tool designed for analyzing leaf nutrient concentrations of Florida citrus. Written by Arnold Schumann and published by the UF/IFAS Department of Soil and Water Sciences.